Plan de mejoramiento para el diseño de un estudio preliminar para la diversificación de productos para la empresa EMAG S.A.S. (2023)
The purpose of this study is to propose an improvement plan as a result of the different activities and action plan applied to the company EMAG S.A.S. during the business practices as a student of international trade, in order to establish a market study which allows the improvement, diversification of its products for the expansion of the company EMAG S.A.S. in national and international markets, implementing different strategies and relevant observations to achieve economic strengthening, taking advantage of the advantages and benefits of venturing into international trade. That is why it is intended to implement the appropriate tools to identify opportunities for a better participation in the market and that EMAG S.A.S. can be recognized through different commercial sectors. For this, it is important to identify the problems and limitations that have prevented the commercial expansion at a national level; in the same way, to take advantage of the products that are already commercialized such as fatty acid and olein to obtain products derived from them and thus expand the sales portfolio. Therefore, an increase in the diversification of products in the portfolio of the company EMAG S.A.S, and to expand in the national markets through commercial strengthening strategies, which would have a direct and positive effect on its competitiveness. Finally, it is intended to identify groups of products with potential for commercial activity in Magdalena and competitiveness by analyzing the behavior of national demand by department and the reception they have had in recent years